Understanding the dangers of long-term corticosteroid use - Ismawi, Hidayatul Radziah (The Malaysian Medical Gazette, 2024)
Corticosteroids are a class of steroid hormones that are produced in our adrenal cortex. They can also be synthetically manufactured and used as medications. Corticosteroids are involved in a wide range of physiological processes, including stress response, immune response, inflammation regulation, carbohydrate metabolism, protein catabolism, blood electrolyte levels, and behaviour.